Paper citizens how illegal immigrants acquire citizenship in developing countries - Sadiq, Kamal (New York ; Oxford : Oxford University Press, 2009)
Rendered in vivid detail,'Paper Citizens' not only shows how illegal immigrants acquire false papers, but also sheds light on the consequences this will have for global security in the post 9/11 world.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Illegal aliens -- South Asia; Illegal aliens -- Southeast Asia; Illegal aliens -- Pakistan; Security, International; Border crossing; South Asia -- Emigration and immigration; Southeast Asia -- Emigration and immigration; Pakistan -- Emigration and immigration